Número natural: conhecimentos de/para professores polivalentes em um curso de especialização - Lamberti, Denise Di Giovanni (2014)
This study investigated knowledge on natural number, offered and achieved by the teachers-students in the discipline Construction of the logic-mathematical knowledge, in a specialized course, semipresential, "Psychopedagogy with a classroom focus", held by the first time in 2011, in the city of Regente Feijó-SP. This is a case study with a documentary character of a qualitative nature which analyzed the course s schedule content, the textbook, the video classes and the responses written by the teachers-students of the investigated discipline. The discipline was analyzed on the knowledge concerning the natural number, by several theoretical contributions and the schedule content by only one of them. The study revealed the course s multiplicity characteristics, setting the teacher s base knowledge required for teaching action, also showing limitations. It considered that the allocated time for the discipline focused on mathematics education should be higher so that it includes reflection and relationship among treated subjects and teacher practices, for the development of necessary knowledge for the teaching occupation. From theoretical frameworks, that seek to the continuous search of knowledge development of teaching occupation on: natural number, number sense, algebraic thinking, psychopedagogic action, learning and constructivism, this study brings contributions to the investigated discipline and to the course, in varied perspectives, with a common goal: the communities establishment where interlocutors (students, teachers, researchers, tutors) can study and reflect on the subject, practice and reflect on the practiced, finally learn and learn how to learn, developing professionally, individually and collectively. This study falls in the Capes Teaching Area